1987
DOI: 10.1093/infdis/155.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Strain AD169 and a Clinical Isolate of Cytomegalovirus with Peripheral Monocytes: The Effect of Lipopolysaccharide Stimulation

Abstract: The effect of human cytomegalovirus (CMV) infection on lipopolysaccharide (LPS)-stimulated and unstimulated monocytes from seronegative donors was studied by using the laboratory-adapted strain AD169 and a recent clinical isolate. LPS-stimulated and unstimulated monocytes infected with the isolate showed expression of immediate-early CMV antigens and were significantly more suppressive for lymphocyte proliferation than were strain AD169-infected monocytes, which rarely expressed detectable viral protein. Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…4 B) were negative. This rate of (nonproductive) infection corresponds closely to rates ( 1% to 9%) previously reported (33,34), although it is considerably lower than the 40% recently reported by others (35). Among monocytes in the CMV-exposed cultures, 1 per 102 to 1 per 103 monocytes expressed TNF-a transcripts (Fig.…”
Section: Methodssupporting
confidence: 89%
“…4 B) were negative. This rate of (nonproductive) infection corresponds closely to rates ( 1% to 9%) previously reported (33,34), although it is considerably lower than the 40% recently reported by others (35). Among monocytes in the CMV-exposed cultures, 1 per 102 to 1 per 103 monocytes expressed TNF-a transcripts (Fig.…”
Section: Methodssupporting
confidence: 89%
“…Since the genes for TNF-a and IL-lI3 are regulated independently, it is not surprising that HCMV did not elicit the release of IL-lIf. It should be pointed out, however, that other investigators have shown that the interaction of HCMV with PBMC from seronegative donors is associated with the production of an IL-l inhibitor (33,34) which may play an important role in the immunosuppressive properties of HCMV (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that viral infections can impair MO/M cytokine production in response to LPS stimulation (1,9,13,26,36,37,56,58). We therefore investigated LPS-stimulated cytokine secretion by DV-infected human MO/M.…”
Section: Effect Of Lps On DV Replication and Induction Of Ifn-␣ Viramentioning
confidence: 99%
“…It has been demonstrated that infection with certain viruses impairs the production of cytokines by MO/M in response to bacterial stimulation (1,9,13,26,36,37,56,58). This mechanism of virally induced, MO/M-mediated immunosuppression may partly account for the detrimental outcome of viral infection followed by a superinfection with bacterial pathogens.…”
mentioning
confidence: 99%